2009
DOI: 10.1037/0096-1523.35.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Subjective patterns of randomness and choice: Some consequences of collective responses.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. from, e.g., game theory and subjective-complexity research, are discussed. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 61 publications
9
59
0
3
Order By: Relevance
“…Teigen (1984) found that subjectively arranged patterns were judged to be slightly more attractive the truly random ones and this difference grows with the complexity. In addition, Falk, Falk, and Ayton (2009) suggest that people's spontaneous responses are affected by their image of randomness as well as by esthetic preferences. However, this connection as well as that in the color setting has yet to be understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teigen (1984) found that subjectively arranged patterns were judged to be slightly more attractive the truly random ones and this difference grows with the complexity. In addition, Falk, Falk, and Ayton (2009) suggest that people's spontaneous responses are affected by their image of randomness as well as by esthetic preferences. However, this connection as well as that in the color setting has yet to be understood.…”
Section: Resultsmentioning
confidence: 99%
“…These are regularities which would be characteristic of natural scenes and, therefore, would represent the statistical evidence that the array-producing process is regular (as opposed to random). For each of these characterizations of subjective randomness, high subjective complexity in binary sequences ⁄ grids is highly correlated with higher-than-normal alternation rates (Bar-Hillel & Wagenaar, 1991;Falk, 1981;Sanderson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The avoidance of the highest-prize lottery may also be related to the general tendency to prefer middle options to options located at the extremes (e.g. Christenfeld, 1995;Falk, Falk, and Ayton, 2009). It is likely that various considerations cross the mind in such situations, as reflected in the interpretation of this avoidance by participants (Study 1).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is a "seeker advantage" because the seekers win more often than predicted by Nash equilibrium (which predicts a 25% seeker win rate from random matching). 3 An important paper by Falk, Falk, and Ayton (2009) collected a lot of data in paradigms similar to the four letter choice. One paradigm consisted of choosing 3 cells out of the 25 locations in a 5x5 matrix.…”
Section: B Previous Evidence Of Focality In Gamesmentioning
confidence: 99%